The Scintigraphic Diagnosis of Stress Fractures in the Lower Extremity - Sriprapaporn, MD, J (Journal of Southeast Asian Orthopaedics, 2022)
Stress fractures are usually found in athletes and military populations. They occur more commonly in the lower extremity. The most commonly involved bone is the tibia, and is frequently associated with running activities. Diagnosis is often difficult, and may be missed due to the limited sensitivity of plain radiographs. Magnetic resonance imaging (MRI) is the gold standard for the diagnosis of stress fractures. Three-phase radionuclide bone scintigraphy is another imaging modality: it is highly sensitive, simple and safe. Thus, it can be used solely, or complementary to MRI.